Students’ Search Behaviors and Career Alignment for Internships - Michael Odio (Journal of Applied Sports Management, 2017)
The present study explores the internship search behaviors of undergraduate sport management students at three public universities, including how much time is spent looking for internships, what resources are used for searching, and what criteria are used when deciding on an internship. The findings affirm previous research that factors such as compensation, location, timing, and career goals are important, but also reveal how students weigh these factors and how it affects when, where, and how they search for internship opportunities. This information is beneficial for employers interested in understanding the student’s perspective of the internship search in order to increase the size and quality of their candidate pool. Subscribe to JASM
Keywords: Sport management internships; recruiting; intern compensation